(3GdYdGeGJ GdJLGQjI hGdfeGPL GdUfGYjI aj Ohd eLdS GdJYGhf GdNdjLjs - (3hGFd CfhQ(B, (3HfObs ((3GdEScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2006)
(3GdYdGeGJ GdJLGQjI aj GdSYhOjI(B-(3GdYdGeGJ GdJLGQjI aj GdHMQjf (B-(3GdYdGeGJ GdJLGQjI aj GdEeGQGJ(B-(3GdYdGeGJ GdJLGQjI aj GdchjJ(B-(3GdYdGeGJ GdJLGQjI aj SdWfI YeGf(B-(3GdYdGeGJ GdJLGQjI aj bWQ(B-(3eYGgOI bGfhf GdYdGeGJ hdGFMI JfajPgGs
Keywords: (3GdLQGFe hGdYbhHGJs; (3GdYdGeGJ GdJLGQjIs